Enzymatic regioselective and complete deacetylation of two arabinonucleosides - Sabaini, María Belén (2010)
Candida antarctica lipase B (CAL-B)-catalysed regioselective deacetylation of 2′,3′,5′-tri- O-acetyl-1-β- d-arabinofuranosyluracil (1) and 2′,3′,5′-tri- O-acetyl-9-β- d-arabinofuranosyladenine (2) was studied. The choice of the reaction medium allowed the regioselective formation of products bearing different degree of acetylation: in isopropanol, CAL-B catalysed the formation of the corresponding 2′- O-acetylated arabinonucleosides, while hydrolyses afforded the 2′,3′-di- O-acetylated products. In particular, the procedure herein described allows a simple and efficient preparation of the reported vidarabine prodrug 2′,3′-di- O-acetyl-9-β- d-arabinofuranosyladenine, avoiding the utilisation of protective groups. Moreover, to achieve full deacetylation of the assayed substrates, a set of commercial hydrolases and fungal keratinases from Doratomyces microsporus (DMK) and Paecilomyces marquandii (PMK) were tested. While only PMK and DMK catalysed the quantitative complete deacetylation of 1, DMK accomplished full deacetylation of 2 in shorter time than the other assayed enzymes.